Use of ICTs to confront climate change: analysis and perspectives - Escobar-Teran, Freddy; Zapata, Jose; Briones, Felipe; Rosero, Marcelo; Portilla, Jorge (Frontiers in Climate, 2025)
The effects of climate change, including temperature and precipitation changes, the retreat of ice sheets, and rising sea levels are more evident today. It emphasizes that greenhouse gases are the primary drivers of these changes. In this context, some international organizations such as the United Nations (UN) and others have been making significant efforts to combat these effects and have considered information and communication technologies (ICTs) as an alternative for monitoring and mitigating climate change. However, the role of ICTs in climate change has not been analyzed in detail. Accordingly, this article presents research progress on the role of ICTs in climate change monitoring and evidence that ICTs are effective tools for reducing greenhouse gas emissions from different sectors. Additionally, this article provides a cost-benefit analysis of ICT applications in various sectors, emphasizing the Sustainable Development Goals (SDGs).